Acciones de enfermería y su influencia en la prevención de los determinantes sociales de parasitosis intestinales en niños menores de 12 años de la Escuela Francisco Pizarro. Recinto Pita. Cantón Caluma. Provincia Bolívar. Octubre 2019-Marzo 2020. - Águila Santillán, Elvis Darwing (2020)
Introduction: Parasitic diseases are considered a major public health problem, mainly affecting children by causing severe pictures of malnutrition, alteration in pondostual and intellectual development. Objective: analyze the influence of nursing actions in the prevention of social determinants of intestinal parasitosis in children under 12 years of the Francisco Pizarro School of the Pita Canton Caluma Campus in the Bolivar province in the period from October 2019 to March 2020. Methodology: Field study, exploratory, descriptive and transversal, with a qualitative approach. Intentional non-probabilistic sampling was carried out, with criteria of inclusion and exclusion. Direct unstructured scientific observation techniques, surveys and a coproparasitological examination for diagnosis were applied. Results: Of a sample of 56 school-age children, 50 were parasitized. It was established by means of the co-epidemiological tests carried out that there was a higher prevalence of monoparasitic children (76,00 %), the majority of parasitic infections caused by helminths, such as Ascaris lumbricoides (30.00 %) and Ancilostomideos (22.00 %) followed by certain protozoa, such as Blastocystis hominis (58,00 %) and Giardia lamblia (50,00 %). In addition, it was found that 62.50 % of the community was not part of any disease prevention and health promotion programme carried out by nursing staff. Conclusions: Social determinants influencing the presence of intestinal parasitosis include inadequate hygiene habits, lack of basic services and poor health education available to the population.